The Development of a Situation-Specific Nurse-Led Culturally Tailored Self-Management Theory for Chinese Patients With Heart Failure. (January 2022) - Jin, Yuanyuan; Peng, Youqing
Introduction: Self-management is essential for treating heart failure (HF). Culture influences the ability to cope, negotiate, and adopt self-management behaviors. However, current HF self-management interventions for Chinese patients do not take culture into consideration. The aim of this article is to describe the development of a situation-specific nurse-led culturally tailored self-management theory for Chinese patients with HF. Methodology: An integrative approach was used as theory development strategy for the situation-specific theory. Results: Based on theoretical and empirical evidence, and theorists' experiences from research and practice, a nurse-led culturally tailored self-management theory for Chinese patients with HF was developed. Discussion: Researchers addressing health phenomena often have difficulty defining, conceptualizing, and operationalizing culture. The situation-specific theory developed in this study has the potential to increase specificity (i.e., logical adequacy and usefulness) of existing theories while informing the application to nursing practice. Further critique and testing of the situation-specific theory is warranted.